The Clinical Factors Associated with Clazosentan Discontinuation and Exploratory Associations with Discharge and Six-Month Outcomes in Aneurysmal Subarachnoid Hemorrhage: A Multicenter DCI Japan Registry Study - Yusuke Inoue; Masahito Katsuki; Toshikazu Hidaka; Yukishige Hashimoto; Yusuke Yamamoto; Daizo Ishii; Katsumi Takizawa; Yoji Tanaka; Masaki Chin; Motohiro Morioka; Hiroki Kurita; Takatoshi Sorimachi; et al. (Journal of Clinical Medicine, 2026)
Background/Objectives: Subarachnoid hemorrhage (SAH) is a life-threatening condition frequently complicated by cerebral vasospasm (VS). Clazosentan has been shown to reduce the incidence of VS and improve outcomes in Japanese studies, and it has been available in Japan since January 2022. However, clazosentan has been associated with systemic adverse events, sometimes leading to discontinuation. This retrospective observational study investigated clinical variables associated with clazosentan discontinuation. Methods: We analyzed data from the multicenter “Database of Cohort Study for Outcome of SAH in Japan” (DCI Japan), prospectively collected from 2020 to 2024. Patients with aneurysmal SAH who underwent surgical clipping or endovascular coiling less than 4 days from onset were included. Multivariable logistic regression was used to investigate variables associated with clazosentan discontinuation. Secondary exploratory analyses examined clinical variables associated with poor functional outcomes (modified Rankin Scale [mRS] 3–6) at discharge and 6 months. Results: Among 372 patients treated with clazosentan (mean age 64.2 ± 14.3 years; 72.6% female), 91.7% (341/372) completed clazosentan during the VS phase, while 8.3% (31/372) discontinued clazosentan prematurely, mainly due to pulmonary complications. Overall, 8.9% (31/350) developed symptomatic VS, and 46.0% (171/372) had poor outcomes (modified Rankin Scale 3–6) at discharge and 31.4% (106/338) at 6 months. Clazosentan discontinuation was associated with age ≥ 76 years (OR for discontinuation: 2.33, 95% CI 1.03–5.28), World Federation of Neurosurgical Societies Grade V (OR 6.52 [2.70–15.78]), larger aneurysm size (OR 1.15 [1.03–1.29]), Fisher computed tomography group 4 (OR 2.61 [1.08–6.30]), and Fasudil hydrochloride hydrate use (OR 3.96 [1.77–8.87]). Poor functional outcome was more frequent in the discontinuation group than in the completion group both at discharge (83.9% vs. 42.5%, p < 0.001) and at 6 months (82.8% vs. 26.5%, p < 0.001). Clazosentan discontinuation was associated with poor outcome at discharge and at 6 months, although the latter was attenuated in sensitivity analysis. Conclusions: Some factors were associated with clazosentan discontinuation, highlighting the clinical relevance of careful systemic monitoring during clazosentan therapy, particularly in patient populations underrepresented in prior trials.